2007
DOI: 10.1536/ihj.48.97
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide Levels and Cardiac Functional Capacity in Patients With Dyspnea and Isolated Diastolic Dysfunction

Abstract: SUMMARYDiastolic heart failure affects approximately 40%-50% of patients presenting with signs and symptoms of heart failure. The aim of this study was to investigate the relationship between brain natriuretic peptide (BNP) levels and functional capacity in patients admitted with dyspnea and diagnosed with isolated diastolic dysfunction.Fifty-four patients (mean age, 57.4 ± 8.5 years) with class-2 dyspnea with isolated diastolic dysfunction were enrolled. Serum levels of BNP were measured, and peak oxygen cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The study by Serpil, et al revealed that plasma BNP levels provided an indication about the cardiac functional capacity in patients admitted with diastolic dysfunction. 20) Considering these results, we speculate that pitavastatin may improve signs and symptoms of HF.…”
Section: Discussionmentioning
confidence: 86%
“…The study by Serpil, et al revealed that plasma BNP levels provided an indication about the cardiac functional capacity in patients admitted with diastolic dysfunction. 20) Considering these results, we speculate that pitavastatin may improve signs and symptoms of HF.…”
Section: Discussionmentioning
confidence: 86%
“…Also, we did not measure brain natriuretic peptide, the level of which has been recently shown to be indicative of the severity of IDD. 22) Besides being cross-sectional, this study was not a prospective population-based randomized investigation, but rather a retrospective observational study of individuals presenting to outpatient clinics; therefore, the potential for selection bias cannot be excluded. However, besides the aforementioned unique geo-demographic characteristic of the study area, this work was performed at 2 large community-based hospitals, thus this sample may largely represent the typical population with cardiac dysfunction seen by a general practitioner.…”
Section: )mentioning
confidence: 99%
“…Kruger et al (34) have also found negative correlation between serum BNP level with PVO 2 and AT values in 70 patients with congestive heart failure. Eroğlu et al (35) evaluated the relationship between BNP levels and CPET parameters in patients with dyspnea and isolated left ventricle diastolic dysfunction and found negative correlation between BNP levels and duration of exercise, AT VO 2 , and MET on CPET. To the best of our knowledge, this is the first study using CPET, and BNP levels in COPD patients.…”
Section: Discussionmentioning
confidence: 99%